Periodic Fluctuations in the Incidence of Gastrointestinal Cancer - Rhyu, Mun-Gan; Oh, Jung-Hwan; Kim, Tae Ho; Kim, Joon-Sung; Rhyu, Young A; Hong, Seung-Jin (Frontiers in Oncology, 2021)
Purpose: Native stem cells can be periodically replaced during short and long epigenetic intervals. Cancer-prone new stem cells might bring about periodic (non-stochastic) carcinogenic events rather than stochastic events. We investigated the epigenetic non-stochastic carcinogenesis by analyzing regular fluctuations in lifelong cancer incidence. Materials and Methods: Korean National Cancer Screening Program data were collected between 2009 and 2016. Non-linear and log-linear regression models were applied to comparatively evaluate non-stochastic and stochastic increases in cancer incidence. Prediction performances of regression models were measured by calculating the coefficient of determination, R2. Results: The incidence of gastric and colorectal cancers fluctuated regularly during both short (8 years) and long (20 years) intervals in the non-linear regression model and increased stochastically in the log-linear regression model. In comparison between the non-stochastic long-interval model and the stochastic model, R2 values were higher in the non-stochastic model of men with gastric cancer (0.975 vs. 0.956), and in the stochastic model of men with colorectal cancer (0.862 vs. 0.877) and women with gastric cancer (0.837 vs. 0.890) and colorectal cancer (0.773 vs. 0.809). Men with gastric cancer showed a high R2 value (0.973) in the non-stochastic short-interval model as well. Conclusion: Lifelong incidence of gastrointestinal cancer tended to fluctuate during short and long intervals, especially in men with gastric cancer, suggesting the influence of an epigenetic schedule.